The impact of academies on school connectedness, future aspirations and mental health in adolescents from areas of deprivation in London. (2nd October 2018) - Frostick, Caroline; Tong, Jin; Moore, Derek; Renton, Adrian; Netuveli, Gopalakrishnan
ABSTRACT: Research shows that school environment impacts significantly on students' mental health, future aspirations and feelings of school connectedness, which in turn can improve academic outcomes. The UK has seen rising numbers of academy schools in recent years which have been scrutinised for academic performance but overlooked in terms of important aspects of school environment. This study compares outcomes for mental health, school connectedness and future aspirations in low-socioeconomic status adolescents attending academy and non-academy schools. Data came from 1284 11-16yr olds attending 1 of 67 academy or non-academy schools from areas of deprivation in London. A total of 639 complete cases were analysed. Self-reported measures of school connectedness, future aspirations and mental health, including self-esteem, were analysed and compared using linear regression clustered at school level, adjusting for the effects of gender, ethnicity, school year and affluence. Adolescents attending academies were found to have significantly higher levels of school connectedness than those at non-academy schools. No direct effect of academies on mental health or aspirations was found, however school connectedness had a significant, mediating effect on pro-social mental health scores. Academies in this sample can therefore be said to indirectly increase levels of mental health by increasing levels of school connectedness. These findings highlight the importance of school connectedness for adolescent wellbeing and suggest that academies can be more successful in promoting levels of school connectedness which can then impact positively on individual mental health. More work needs to be done on identifying the structures and processes at work.